Stimulus equivalence elucidates how advertisements influence children’s eating behavior (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
The objective was to replicate Santos and de Rose (2018) that investigated the influence of characters on children’s food choices. Two classes of equivalent stimuli were formed, one with a character the child liked (A1) and the other he/she didn’t like (A2). Each class had three stimuli, characters (A1 and A2), geometric figures (B1 and B2), and abstract symbols (C1 and C2). A New Symbol (NS) and an image of a Known Brand (KB) by the child were also used. Thirteen children participated, but just six completed the study. Three tests of choice and preference were conducted between two transparent containers with the same food: C1xC2, C2xNS, and C1xKB. The results replicated Santos and de Rose (2018) in Test 1 and in part of Test 2 and were different in Test 3. The Stimulus Equivalence proved to be useful in the study of variables that determine children’s food choices.